A taxonomic review of the genus Palumbina Rondani, 1876 (Lepidoptera, Gelechiidae, Thiotrichinae) from China, with descriptions of twelve new species - Lee, Ga-Eun; Li, Houhun; Han, Taeman; Park, Haechul (Zootaxa, 2018)
Palumbina is a small genus of Gelechiidae that includes species distributed only in the Old World. It was recently assigned to the subfamily Thiotrichinae, but the morphological and molecular studies at the species level have not been extensively conducted. In this study, we focused on the taxonomy of the Chinese Palumbina using morphology and DNA barcoding analysis to confirm the species identification and the relationship among closely related species. In China, three species of this genus were recorded previously. A total of 19 were finally recognized in the present study, including 12 new species: P. magnisigna sp. nov., P. grandiunca sp. nov., P. melanotricha sp. nov., P. atricha sp. nov., P. sigmoides sp. nov., P. acuticula sp. nov., P. rugosa sp. nov., P. sineloba sp. nov., P. spinevalva sp. nov., P. acerosa sp. nov., P. triangularis sp. nov. and P. acinacea sp. nov., and five species that are new records for China: P. chelophora (Meyrick, 1918), P. diplobathra (Meyrick, 1918), P. macrodelta (Meyrick, 1918), P. nesoclera (Meyrick, 1929) and P. operaria (Meyrick, 1918). Three new combinations are proposed: P. operaria (Meyrick, 1918) comb. nov., P. albilustra (Walia et Wadhawan, 2005) comb. nov. and P. shivai (Walia et Wadhawan, 2005) comb. nov., and one new synonymy is established: Thyrsostoma albilustra (Walia et Wadhawan, 2005), syn. nov. of P. oxyprora (Meyrick, 1922). Based on the neighbor-joining analysis of COI gene sequences of 67 exemplar specimens, four clades were well supported with high bootstrap values resulting in four species-groups: the guerinii-group, the grandiunca-group, the macrodelta-group and the nesoclera-group. However, seven species were grouped together in an additional clade with weak support and P. diplobathra and P. chelophora were not clustered with any other species due to the high genetic divergences. Palumbina chelophora showed typical characteristics of the genus morphologically, but it was not embedded within Palumbina as monophyletic from the tree, assuming that the sole use of mitochondrial fragments could not resolve the deeper relationship. Therefore, further investigation is needed to clarify those issues. In this study, the generic diagnosis was reviewed based on previous studies and morphological examination.